2017
DOI: 10.1063/1.4989834
|View full text |Cite
|
Sign up to set email alerts
|

Noise, gain, and capture probability of p-type InAs-GaAs quantum-dot and quantum dot-in-well infrared photodetectors

Abstract: We report experimental results showing how the noise in a Quantum-Dot Infrared photodetector (QDIP) and Quantum Dot-in-a-well (DWELL) varies with the electric field and temperature. At lower temperatures (below $100 K), the noise current of both types of detectors is dominated by generation-recombination (G-R) noise which is consistent with a mechanism of fluctuations driven by the electric field and thermal noise. The noise gain, capture probability, and carrier life time for bound-to-continuum or quasi-bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, the low production yield and high cost become the bottleneck for further upgrading the HgCdTe-based infrared imaging systems [4]. Over the past two decades, the demand for the third-generation infrared imaging systems brings interests in quantum structures [5][6][7][8][9]. Particularly, III-V quantum structures have been considered as a candidate that could compete with MCT in terms of performance and cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low production yield and high cost become the bottleneck for further upgrading the HgCdTe-based infrared imaging systems [4]. Over the past two decades, the demand for the third-generation infrared imaging systems brings interests in quantum structures [5][6][7][8][9]. Particularly, III-V quantum structures have been considered as a candidate that could compete with MCT in terms of performance and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1993, self-assembled quantum dots (QDs) grown by the Stranski-Krastanow (S-K) strain relaxation have gained great attention due to their possible optoelectronic device applications, such as semiconductor lasers, amplifiers, modulators, photovoltaic, and infrared photo-detectors [1][2][3][4][5][6]. As examples, QD hybrid structures with QDs coupled to a quantum well (QW) have been exploited in various material systems and optoelectronic devices where additional excess carriers can be provided through carrier transfer from the QW [7][8][9][10][11][12][13][14]. There are at least two ways to fabricate such QD hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 It was shown that the insertion of InAs QDs into InGaAs capping/buffer QWs, named as dot-in-well structures, allows the emission intensity of the InAs QDs to be varied and changed the positions of the GS peaks, as well as the QD sizes and QD surface densities. [15][16][17][18] InAs QDs grown within the symmetric In x Ga 1-x As QWs on the GaAs substrate with the InAs molar fraction x = 0.1-0.3 in QWs were characterized by 1.5-fold larger the lateral QD sizes compared with InAs/GaAs QDs. 15 However, the QD heights and surface densities were the same in both cases.…”
mentioning
confidence: 99%
“…The higher QD emission intensity is detected owing to the more efficient carrier capture by QDs in the dot-in-well structures. [15][16][17] Therefore, the dot-in-well structures had better emission properties, in comparison with InAs QDs within a GaAs matrix, and the emission of the QDs was tuned to the communication important wavelength of 1.3 μm.…”
mentioning
confidence: 99%
See 1 more Smart Citation